Navigating Blood Donation Challenges in India Amid COVID-19: A Comprehensive KAP Analysis - Kaur, Pandeep; Jain, Romesh; Kumar, Rakesh; Bhaskar, Bala; Kumar, Satish; Ranjan, Shweta (Disease and Health Research: New Insights Vol. 3, 2024)
Background: An awareness of knowledge, attitudes, and practices (KAP) of blood donors towards the COVID-19 pandemic is essential to avoid a blood inventory crisis. It is therefore necessary to gain a perspective on the impact of COVID-19 on the attitude of blood donors and an understanding of the key aspects of their motivation. The study aimed to analyze the KAP of donors toward blood donation and to find their association with the demographic factors, aiding in mobilizing and retaining voluntary blood donors in a pandemic setting. Methods: A prospective longitudinal study was conducted at The Department of Immunohematology and Blood Transfusion at a tertiary care teaching hospital in India over four months spanning from December 2021 to March 2022 on repeat whole blood donors. A survey-method was used to collect data in the form of donor responses to questionnaires circulated via emails, instant messaging services (Whatsapp, Telegram etc.) and social media sites (Facebook, Twitter etc.). All the classification variables (age, sex, education, income and occupation) were expressed as frequency and percentage. Results: A total of 632 donors were included in the study and assessed for donor attitude and fear factors related to blood donation during COVID-19 pandemic. The mean age of the study population was 31 years. In terms of donor attitude, most common positive attitude was that they “would donate blood in the blood center where mask and sanitizer are available for all staff and blood donors”. Most common negative attitude was that “they had been in close contact with a patient who had a respiratory infection, so they should not donate blood”. Regarding practice of blood donation, 61.9% donors reported that they did not attend blood bank due to uncertainty about the sanitization of blood bank. The most common responses about knowledge were that they feared contracting COVID-19 during blood donation (41.5%) and they had fear of post-COVID-19 complications (37.5%). Conclusions: To enhance precautionary behaviors among the public, health officials and policymakers must promote knowledge and efficacy beliefs about blood donation. Future interventions and policies should adopt a 'donor-centered' approach to close the gaps in KAP related to blood donation, ultimately motivating and retaining blood donors.